2022
DOI: 10.3389/fchem.2022.912822
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Thiazolidine-2,4-dione Derivatives and Their Lipoxygenase Inhibition Activity With QSAR and Molecular Docking Studies

Abstract: Thiazolidinediones are five-membered, heterocyclic compounds that possess a number of pharmacological activities such as antihyperglycemic, antitumor, antiarthritic, anti-inflammatory, and antimicrobial. Conventional methods for their synthesis are often environmentally unacceptable due to the utilization of various catalysts and organic solvents. In this study, deep eutectic solvents were used in the synthesis of thiazolidinedione derivatives that acted as both solvents and catalysts. Initially, a screening o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Compounds 8-11 have recently been synthesized in another DES by Loncaric et al [25]. The corresponding aldehydes were reacted with TZD in ChCl:N-methylurea (1:3) at 80 C until completion of the reaction monitored by TLC (precise times were not indicated).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Compounds 8-11 have recently been synthesized in another DES by Loncaric et al [25]. The corresponding aldehydes were reacted with TZD in ChCl:N-methylurea (1:3) at 80 C until completion of the reaction monitored by TLC (precise times were not indicated).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that glycerol can form a strong hydrogen bonding network in a DES, being here an H‐bond donor and L‐proline being an H bond acceptor [32, 33]. A plausible mechanism often proposed by the authors [25, 27–31] involves the activation of carbonyl group by the DES (Scheme 1). Another point to be considered is the fact that it is well established that L‐proline forms iminium ion with aldehyde to catalyze Knoevenagel condensation [34, 35] (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Thiazolidine-2,4-diones are an important class of heterocycles that present a diverse range of biological activities. 15,16 These heterocycles are of particular importance in the development of novel anti-diabetic agents. Glitazones consist of a class of active pharmaceutical ingredients (APIs), with a thiazolidine-2,4dione core in their structure, which are widely used for the treatment of type 2 diabetes.…”
mentioning
confidence: 99%